2023
DOI: 10.3390/cancers15030959
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal LncRNAs in Gastrointestinal Cancer: Biological Functions and Emerging Clinical Applications

Abstract: Due to the lack of specific and effective biomarkers and therapeutic targets, the early diagnosis and treatment of gastrointestinal cancer remain unsatisfactory. As a type of nanosized vesicles derived from living cells, exosomes mediate cell-to-cell communication by transporting bioactive molecules, thus participating in the regulation of many pathophysiological processes. Recent evidence has revealed that several long non-coding RNAs (lncRNAs) are enriched in exosomes. Exosomes-mediated lncRNAs delivery is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…In recent years, the study of exosomes as important mediators of cell communication has emerged endlessly [88,89]. Exosomes facilitate communication with recipient cells through various mechanisms, including ligand binding directly to the receptor to activate downstream signaling, direct membrane fusion resulting in the release of exosome contents into the recipient cells, and internalization of exosomes by the recipient cells through endocytosis (including phagocytosis, macrophage, or receptor-mediated endocytosis) [90].…”
Section: Function Of Exosomesmentioning
confidence: 99%
“…In recent years, the study of exosomes as important mediators of cell communication has emerged endlessly [88,89]. Exosomes facilitate communication with recipient cells through various mechanisms, including ligand binding directly to the receptor to activate downstream signaling, direct membrane fusion resulting in the release of exosome contents into the recipient cells, and internalization of exosomes by the recipient cells through endocytosis (including phagocytosis, macrophage, or receptor-mediated endocytosis) [90].…”
Section: Function Of Exosomesmentioning
confidence: 99%
“…When determining the mechanism of action, it was proposed that hsa_circ_0000069 acts as a sponge for miR-144 by increasing the expression of the STIL gene by the main regulator of the mitotic centrosome [56]. In addition to circulating RNAs, it has been shown that gastric cancer cells secrete exosome-packaged long noncoding RNA (lncRNA) SND1-IT1 [57]. Internalization of this lncRNA by human gastric mucosa epithelial GES-1 cells caused cell malignant transformation by enhancing the expression of ubiquitin-specific protease 3 (USP3), inhibiting miR-1245b-5p, and simultaneously recruiting DEAD-box helicase 54 (DDX54).…”
Section: Cancer-derived Evs Transform Normal Cells Into Cancer Cellsmentioning
confidence: 99%
“…The stability can be explained by their packing in extracellular vesicles such as apoptotic bodies, microvesicles, and exosomes. Circulating exosomal lncRNAs have emerged as promising biomarkers for GC ( Zhang et al, 2021 ; Badowski et al, 2022 ; Sun et al, 2023 ).…”
Section: Key Biological Features and Mechanisms Of Lncrnasmentioning
confidence: 99%
“…In GC, these transcripts play a crucial role in promoting carcinogenesis through the modulation of cellular mechanisms, such as proliferation, stemness, tumor immune escape, invasion, angiogenesis, and drug resistance of tumor cells ( Zhang X.-Z. et al, 2020 ; Gui et al, 2021 ; Jiang et al, 2021 ; Razavi et al, 2021 ; Sun et al, 2023 ).…”
Section: Exploring the Role Of Lncrnas In The Regulation Of Gc Develo...mentioning
confidence: 99%